OR34-01 11C Metomidate PET-CT Identifies More Unilateral Primary Aldosteronism Than Adrenal Vein Sampling - Puar, Troy (J Endocr Soc, 2020)
Introduction. Adrenal vein sampling (AVS) is the current reference test to identify unilateral, surgically-curable primary aldosteronism (PA). However, AVS is invasive and technically difficult. Even in AVS-proven unilateral PA, up to 6% of patients with fail to have biochemical cure after surgery using the PASO criteria. 11C-Metomidate PET-CT offers a non-invasive alternative. We compared the accuracy of both PET-CT and AVS using post-surgery cure (PASO criteria) as the reference. Methods. This multi-centre prospective trial recruited 25 patients with confirmed PA, and all underwent CT, AVS, and PET-CT tests. Sequential AVS under ACTH-stimulation was done by an experienced interventionalist, and cortisol gradient of >5 was taken to be successful cannulation. Lateralization ratio >4 was consistent with unilateral PA. All results were reviewed at a multidisciplinary meeting to decide on the diagnosis (unilateral or bilateral PA) and management (secondary outcome). Primary outcome was biochemical cure using PASO criteria at 6 months post-surgery (ClinicalTrials.gov: NCTxxxxxxxx). Results. Recruitment for the study has been complete with 25 patients, 49.2 ± 9.5 yr, 14 females (56.0%). All 25 patients had successful AVS. 22 of 25 patients (88.0%) had unilateral PA, and 3 patients (12.0%) had bilateral PA. PET-CT identified unilateral PA in 18 of 22 patients (sensitivity 81.8%), while AVS identified unilateral PA in 15 of 22 patients (sensitivity 68.2%). In one patient, repeat AVS done simultaneously without ACTH-stimulation aided to identify unilateral PA, when initial AVS failed to do so. Other cases where AVS failed to identify unilateral PA were due to venous anomalies, and limitation of the lateralization cut-off of 4. 18 of 22 patients have undergone surgery, with 3 patients awaiting surgery, and 1 opting for medical treatment. Post-surgery, all patients had complete normalization of aldosterone-renin ratio, and hypokalemia (if present). 2 patients had bilateral PA on both PET-CT and AVS. 1 patient had discordant AVS and PET-CT results, with AVS lateralizing to right, and PET-CT to left. This patient was classified as bilateral PA and treated medically. Conclusion. This is the first study to demonstrate that 11C-Metomidate PET-CT may identify cases of unilateral PA not detected with AVS, using the stringent PASO criteria for post-operative biochemical cure.